Prenatal Drug Exposure in Children With a History of Neuropsychiatric Care: A Nested Case-Control Study - Benevent, Justine; Hurault-Delarue, Caroline; Araujo, Mélanie; Revet, Alexis; Sommet, Agnès; Lacroix, Isabelle; Damase-Michel, Christine (Frontiers in Psychiatry, 2022)
Background and Objectives Neuropsychiatric disorders in childhood after prenatal drug exposure raises concerns. Most of the published studies focused on psychotropic medications. This study investigated which prenatal medication exposure was associated with neuropsychiatric disorders in childhood. Methods A case-control study, nested in the French POMME cohort, was conducted to compare prenatal medication exposure between children with a history of neuropsychiatric care (ages 0–8 years) and children in a control group. POMME included children born in Haute-Garonne to women covered by the general Health Insurance System, between 2010 and 2011 (N = 8,372). Cases were identified through: (1) reimbursement for neuropsychiatric care; (2) psychomotor development abnormalities specified on health certificates; and (3) reimbursement for methylphenidate or neuroleptics. Controls had none of these criteria. Prenatal exposure to each of the major “Anatomical Therapeutic Chemical” classes was compared between the groups. Class(es) for which there was a statistically significant difference (after Bonferroni adjustment, i.e., p < 0.0033) was(were) compared using logistic regression. Results A total of 723 (8.6%) cases and 4,924 (58.8%) controls were identified. This study showed a statistically significant difference in prenatal exposure to nervous system drugs (excluding analgesics) between the groups [ORa: 2.12 (1.55; 2.90)]. Differences (not statistically significant at the 0.0033 threshold) were also observed for the ATC classes: Musculoskeletal, Genito-urinary System and Sex Hormones, Alimentary Tract and Anti-infectives. Conclusion Through identification of children with neuropsychiatric disorders and of their prenatal medication exposure, this study provides guidance for the assessment of long-term neuropsychiatric effects after prenatal medication exposure, without focusing on psychotropic medications.